Excitability at the motoneuron pool and motor cortex is specifically modulated in lengthening compared to isometric contractions - Gruber, M.; Linnamo, V.; Strojnik, V.; Rantalainen, T.; Avela, J. (Journal of Neurophysiology, 2009)
Neural control of muscle contraction seems to be unique during muscle lengthening. The present study aimed to determine the specific sites of modulatory control for lengthening compared to isometric contractions. We used stimulation of the motor cortex and corticospinal tract to observe changes at the spinal and cortical levels. Motor evoked potentials (MEPs) and cervicomedullary motor evoked potentials (CMEPs) were evoked in biceps brachii and brachioradialis during maximal and submaximal lengthening and isometric contractions at the same elbow angle. Sizes of CMEPs and MEPs were lower in lengthening contractions for both muscles (by ~ 28% and ~ 16%, respectively; p < .01) but MEP to CMEP ratios increased (by ~ 21%; p < .05). These results indicate reduced excitability at the spinal level but enhanced motor cortical excitability for lengthening compared to isometric muscle contractions.